L’ancrage local des référentiels normatifs globaux : une approche en terme de réseaux - Nathalie Semal (VertigO, 2005)
The ISO 14001 standard is currently  the worldwide reference for Environmental Management System. For it has been produced at and for international level, how does it become embedded in local situations and  action context.This article highlights the role of expertise in this embedding process in the framework of conceptual and methodological repertory of the sociology of translation. We firstly describe activities and actors that are involved in certification. Then our analyse is focused on triple role of environmental management expertise in embeddedness process of ISO 14001 standard: translation, netting and experience capitalization.